Emulsifying Stability, Digestive Sustained Release, and Cellular Uptake of Alcohol-Soluble Artemisia argyi Flavonoids Were Improved by Glycosylation of Casein Micelles with Oat Glucan - Ye Zhang; Dongliang Wang; Mengling Peng; Min Yang; Ya Yu; Mengting Yuan; Yanan Liu; Bingyu Zhu; Xiuheng Xue; Juhua Wang (Foods)
Flavonoids, widely present in Artemisia argyi (AA), offer potential health benefits but are limited in food applications because of their bitter taste, inadequate absorption, and stability. Casein micelles encapsulation can enhance the flavonoid absorption, stability, and bioactivity. In this study, Artemisia argyi flavonoids (AAFs) were extracted using ultrasound-assisted extraction (UAE) to optimize the process. The glycosylation reaction between casein (CN) micelles and oat β-glucan (OBG) was employed to improve AAF’s emulsifying stability, sustained release during digestion, and cellular uptake. The maximum glycosylation degree of 32.33% was achieved at a CN-to-OBG ratio of 1:2, 120 min browning time, and 95 °C temperature. This glycosylated delivery system enhanced the emulsifying properties of the AAFs, digestive sustained release, and cellular uptake, showing potential as a cross-linking material for fat-soluble substances and medicines.